Інформаціна влада: зміст і значимість у сучасних умовах - Антошина, Ірина Володимирівна; Антошина, І. В.; Antoshyna, Iryna V. (Одеса : Гельветика, 2019)
Формування інформаційної влади безпосередньо пов’язане зі становленням інформаційного суспільства, в якому інформація стає головним економічним ресурсом, а інформаційний сектор виходить на перше місце за темпами зростання. Інтелектуальна власність стає основною формою власності, важливим стає людський капітал; інформація стає предметом масового споживання, формуються нові правові основи функціонування інформаційного суспільства. Тепер свобода слова й інформації на засадах верховенства права та повага прав людини – це основні постулати створення громадянського суспільства, заява про справжню демократію. Тому межі існування інформаційної влади мають бути узгоджені з правами та свободами людини. Отже, право на доступ до інформації стає одним із невід’ємних прав людини та громадянина. Пріоритетним завданням Української держави є забезпечення свободи слова, свободи інформації, права на висловлення думок і позиції громадянина, права на отримання й поширення достовірної інформації без перешкод. Сутність інформаційної влади зводиться до здатності поширення за допомогою засобів масової інформації та міжособистісного спілкування певних ідей. Право на доступ до інформації стає одним із невід’ємних прав людини та громадянина. Пріоритетним завданням української держави є забезпечення свободи слова, свободи інформації, право на вираження думки й позиції громадянина, право на отримання й поширення достовірної інформації без перешкод. Найважливіше значення для подальшого розвитку українського суспільства полягає у взаємодії державної влади з інформаційною владою. У сучасних умовах інформаційна влада визначальним чином впливає на різні сфери суспільного розвитку, що трансформує багато політичних і державних інститутів. Ефективність державної влади багато в чому залежить від усебічного регулювання інформаційних відносин, що визначає характер її взаємодії з інформаційною владою.

In modern conditions the information power directly bind with formation of an information society, in which information becomes the main economic resource, and the information sector comes out on the top on rate of growth. The intellectual property becomes the main form of ownership, a human capital becomes the important; an information becomes a subject of mass consumption, the new legal bases of functioning of an information society are formed. Now, freedom of speech and information on the basis of the rule of law and the respect of human rights are the main postulates of the creation of a civil society, the statement of a real democracy. Therefore, the limits of the existence of the information power have to be agreed with the rights and the freedoms of a person. So, the right for access to information becomes one of inalienable rights of a human and a citizen. A priority task of the Ukrainian state is the ensuring the freedom of speech, the freedom of an information, the right for expression of opinion and the citizen`s position, the right for the receipt and the dissemination of the reliable information without obstacles. The essence of information power comes down to the ability to disseminate through the media and the interpersonal communication of certain ideas. The right to access information becomes one of the inalienable human and citizen rights. The priority task of the Ukrainian state is to ensure freedom of speech, freedom of information, the right to express the opinion and position of a citizen, the right to receive and impart reliable information without hindrance. The most important for the further development of Ukrainian society is the interaction of the state power with the information power. In modern conditions information power has a decisive influence on the various spheres of social development, which transforms many political and state institutions. The effectiveness of state power largely depends on the comprehensive regulation of information relations, which determines the nature of its interaction with the information power.
Антошина І. В. Інформаціна влада: зміст і значимість у сучасних умовах / І. В. Антошина // Юридичний вісник. - Одеса : Гельветика - 2019. - № 4. - С. 14-20.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; information; information society; information space; information power; state power; power resources; information; information society; information space; information power; state power; state resources; right of access to information; right to information; інформація; інформаційне суспільство; інформаційний простір; інформаційна влада; державна влада; ресурси влади; право на доступ до інформації; право на інформацію